Halal Beauty and Global Ethical Consumerism: Integrating Islamic Values into Contemporary Beauty Diplomacy - Arsyad, Rafika; Herdiana, Aan; Ardiansah, Ardiansah; Sufy, Febilita Afra Mutiara (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2026)
This study examines how integrating Islamic values, particularly halalan tayyiban, with vegan and cruelty-free principles in beauty products can serve as a tool to address islamophobia. Using a qualitative research design, this paper combines document analysis with expert consultations from halal certified advisors, academics, government regulatory bodies (BPJPH), industry associations (PERKOSMI), and leading halal beauty brand (Wardah), supplemented by exploratory consumer insights from 100 respondents across Indonesia, Malaysia, and Singapore, including 41 non-Muslim consumers from Buddhist, Christian, Hindu, and Confucian backgrounds. Situates within the frameworks of soft power, cultural diplomacy, and ethical consumerism. The findings reveal that halal beauty products, when aligned with global ethical trends such as sustainability and animal welfare, transcend their commercial role and act as cultural ambassadors, projecting a positive image of Islamic values. Consumer data indicate that 70% of respondents agreed halal products can shift perceptions of Islam, with non-Muslim consumers showing favorable attitudes when halal is framed through universal ethical narratives rather than religious signaling. Expert consultations confirm that while Indonesia faces governance challenges, limiting its global halal market share to 3.6%, industry stakeholders increasingly view halal certification as a competitive advantage that shapes international supply chain standards. The study concludes that halal beauty diplomacy operates through gradual, cumulative influence rather than dramatic perception shifts, and offers recommendations for policymakers, certification bodies, and industry stakeholders to expand the global presence of Islamic value-based beauty products as instruments of peace, inclusivity, and prejudice reduction.